NDT Non-Destructive Test for Quality Evaluation of Concrete specimens by Ultrasonic Pulse Velocity measurement. Issue 1 (May 2020) - Pedreros, L; Cárdenas, F; Ramírez, N; Forero, E
Abstract: Knowing the quality of concrete is very important, because this type of material is part of the design and implementation of most structures such as bridges, buildings, tunnels, among others, in this investigation non-destructive tests were carried out on test specimens of using ultrasound, which were designed and developed in the concrete laboratory at Santo Tomas University in Bogotá D.C. taking into account for its preparation a dosage of the estimated concrete mixture in order to obtain specimens with a compressive strength of 3500psi, 2500psi and 1500psi, in such a way, the specimens were allowed to cure for a period of 28 days, ensuring that they achieved their maximum compression strength. As mentioned above, non-destructive ultrasound tests were applied in order to determine the quality of the manufactured concrete specimens, thus, an ultrasound system is proposed that makes it possible to pass an acoustic wave through a concrete specimen, this was proposed with the purpose of measuring the velocity with which the wave passes in the volume of this material, known as the ultrasonic pulse velocity. Therefore, the respective velocities for each of the concrete specimens were measured, thus finding a relationship between the ultrasonic pulse velocity and the compressive strength, which finally makes possible the evaluation of the manufactured concrete specimens.